Theoretical foundations of socioclinical intervention in organizations (Clinical Sociology Review, 2022)
Clinical sociology offers an approach that breaks with the paradigms stemming from the engineering  and management sciences. The clinical approach is critical in the face of normative, quantitative, prescriptive approaches dominated by instrumental rationality and the commodification of human relations. She is interested in the singular, in subjectivity, in experience, in the sensitive, with an ethical concern. Its objective is to associate the actors concerned with the understanding of the problems, to involve them as subjects in the elaboration of the answers that they bring individually and collectively to the contradictions which cross them. She does not seek to model reality but to immerse herself in lived experience, as close as possible to concrete situations, the reality of work, the subjective apprehension of the problems encountered. It is part of a complex social system. Change is not prescribed, it is built in a process that involves, actively or passively, all the people concerned.
Keywords: clinical sociology×complexity×intervention×conflicts×subjectivity ×organizations×